2000
DOI: 10.1097/00005392-200010000-00078
|View full text |Cite
|
Sign up to set email alerts
|

Cyto-Injury Factors in Urine: A Possible Mechanism for the Development of Interstitial Cystitis

Abstract: Normal human urine contains heat labile, cationic components of low molecular weight that bind to heparin. These components, when separated from the bulk of the urinary wastes, are cytotoxic to urothelial cells as well as underlying smooth muscle cells, indicating their potential for causing bladder mucosal injury. The cytotoxic activity can be blocked by the presence of THP. This urinary cytoprotective activity of THP may play an important but unrecognized role in the development of IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…In our study, markedly increased NGF activity in the bladder wall with significant L6-S1 nNOS, NGF and c-fos expression was determined in instillated bladder with IC urine and normal human urine. According to Parsons et al [26], normal human urine contains heat-labile cationic material of low molecular weight (500-1,000 daltons) that is cytotoxic for uroepithelial cells and smooth muscle cells, Baykara/Erdogru/Gülkesen/Sargın/Savaş/ Ateş and the differences in the protective capacity of TammHorsfall protein may be one of the several factors effecting the balance between detrimental components and bladder defense mechanisms in IC patients. Increased bladder nociceptive activation due to leaky epithelium in IC might be the result of one or more disruptions in the system of normal bladder defense mechanisms owing to impairment of the protective capacity of Tamm-Horsfall protein, an increased level of injurious cation or an abnormality in factors inhibiting regeneration of injured uroepithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, markedly increased NGF activity in the bladder wall with significant L6-S1 nNOS, NGF and c-fos expression was determined in instillated bladder with IC urine and normal human urine. According to Parsons et al [26], normal human urine contains heat-labile cationic material of low molecular weight (500-1,000 daltons) that is cytotoxic for uroepithelial cells and smooth muscle cells, Baykara/Erdogru/Gülkesen/Sargın/Savaş/ Ateş and the differences in the protective capacity of TammHorsfall protein may be one of the several factors effecting the balance between detrimental components and bladder defense mechanisms in IC patients. Increased bladder nociceptive activation due to leaky epithelium in IC might be the result of one or more disruptions in the system of normal bladder defense mechanisms owing to impairment of the protective capacity of Tamm-Horsfall protein, an increased level of injurious cation or an abnormality in factors inhibiting regeneration of injured uroepithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Parsons et al. suggested that cationic urinary components could potentially be cytotoxic to the urothelial cells, resulting in bladder mucosal injury 52,53 . Some dietary metabolites, medications and nutritional supplements also exert cytotoxic effects on the urothelium 26 .…”
Section: Pathophysiology Of Ic/bpsmentioning
confidence: 99%
“…For the most part, their presence in urine may be attributable to secondary responses to the disease process and these are reactive products that are not involved in the initiation of IC. One agent that may be involved in inducing the disease is antiproliferative factor , and others are cationic urinary toxic factors capable of injuring the superficial epithelial cells . Our interest has been in protective factors in urine such as Tamm–Horsfall protein (THP), which reduces disease risk and potential toxic factors that could injure epithelial mucus and increase the risk of IC.…”
Section: Introductionmentioning
confidence: 99%